Utilization of d-Methionine by Escherichia coli - Cooper, Stephen (1966)
Cooper, Stephen (University Institute of Microbiology, Copenhagen, Denmark). Utilization of d-methionine by Escherichia coli. J. Bacteriol. 92:328–332. 1966.—Methionine-requiring strains of Escherichia coli grow on d-methionine. Mutants can be isolated which cannot grow on d-methionine. The d-methionine nonutilizing mutation is independent of the methionine requirement, and maps near the lac region of the E. coli genome. Growth of methionine-requiring strains on d-methionine is dependent upon aerobic conditions. Cells grown on d-methionine have a sixfold greater ability to incorporate d-methionine into protein than cells grown on l-methionine. The incorporation of d-methionine is inhibited by l-methionine.